Investigating the Performance of Closed-end Funds in Mainland China. - Yu, Wenting (2007)
A closed-end fund is a type of professionally managed investment company that provides investors lots of benefits unique in the investment world. As the largest emerging market in the world, China market attracts the focus of the global investors. Many foreign investors are especially interested in the China closed-end fund market because of the persistent large discounts in the past few years. This empirical research evaluated 23 Chinese closed-end funds during the period June 2003 to June 2007. The objective of this study is to evaluate the performance of China's closed-end funds and trying to find whether the closed-end funds outperformed the market. Three famous and traditional performance measures were employed to examine the funds, performance: Sharpe ratio, Treynor ratio and Jensen's alpha. In addition, one-sample t-test was also conducted to estimate the mean difference between the closed-end funds and the market index. The results of the Sharpe ratio suggested that on average China closed-end funds tended to underperform the market index during the research period. However, there were still several funds that could produce positive returns for the fund holders, this possibly due to the market inefficiency in China. Moreover, in terms of one-sample t-test, the Treynor ratio was statistically insignificant. Such results may be acceptable due to the unique characteristics of the Chinese capital market. Furthermore, the research model in this paper was based on the Capital Asset Pricing Model (CAPM), which is widely used by researchers for evaluating the investment fund performance. Nevertheless, many recent empirical studies have found that in practice the model is poor, which did result certain limitations in this research paper.